Apixaban and rivaroxaban's physiologically‐based pharmacokinetic model validation in hospitalized patients: A first step for larger use of a priori modeling approach at bed side - Jean Terrier; Frédéric Gaspar; Pauline Gosselin; Olivier Raboud; Camille Lenoir; Victoria Rollason; Chantal Csajka; Caroline Samer; Pierre Fontana; Youssef Daali; Jean‐Luc Reny; for the OptimAT study group (Wiley, 2023)
Abstract When used in real‐world conditions, substantial interindividual variations in direct oral anticoagulant (DOAC) plasma concentrations are observed for a given dose, leading to a risk of over‐ or under‐exposure and clinically significant adverse events. Physiologically‐based pharmacokinetic (PBPK) models could help physicians to tailor DOAC prescriptions in vulnerable patient populations, such as those in the hospital setting. The present study aims to validate prospectively PBPK models for rivaroxaban and apixaban in a large cohort of elderly, polymorbid, and hospitalized patients. In using a model of geriatric population integrating appropriate physiological parameters into models first optimized with healthy volunteer data, observed plasma concentration collected in hospitalized patients on apixaban (n = 100) and rivaroxaban (n = 100) were adequately predicted (ratio predicted/observed area under the concentration curve for a dosing interval [AUCtau] = 0.97 [0.96-0.99] geometric mean, 90% confidence interval, ratio predicted/observed AUCtau = 1.03 [1.02-1.05]) for apixaban and rivaroxaban, respectively. Validation of the present PBPK models for rivaroxaban and apixaban in in‐patients represent an additional step toward the feasibility of bedside use.